The Influence of Placement and Training on Performance with Competence in Companies Members of the Indonesian Logistics & Forwarders Association (ALFI) - Iman Gandi Mihardja; Masydzulhak Djamil; Ahmad Badawi Saluy (Journal of Accounting and Finance Management, 2023)
Human resources in the logistics sector still have problems in terms of personal abilities, where most of the employees are elementary school graduates. To support employee performance, it is necessary to adjust work placements, training, and competence as mediators. As intervening factors, the study seeks to determine the impact of placement and training on employee performance and competence. The study was conducted at an ALFI member business that has been in the logistics sector for decades. The quantitative method was applied in the study. The sample-to-variable ratio was used to determine the number of samples, and data was analysed using SEM PLS. The results show that the placement variable has a positive effect on competence, the training variable has a positive effect on competence, the placement variable has a positive effect on employee performance, the training variable has a positive effect on employee performance, the placement variable has an influence on employee performance, the competence variable has an indirect effect on employee performance because competence becomes an intervening variable, and the placement variable has an influence on employee performance.